the Study of some histopathological changes occurring in white laboratory mice infected with Cutaneous Leishmaniasis in Al – diwaniyah province, Iraq. - edu, Lubna.A.Al-ibrahimi; Hind Al-shabani; Marwa sami alwan (Al-Qadisiyah Journal of Pure Science, 2021)
Leishmaniasis is caused by an intracellular parasite . It is endemic in Asia, Africa, the Americas, and the Mediterranean region. Worldwide, 1.5 to 2 million new cases occur each year .The histological study of the liver tissue of white laboratory mice (Mus musculus) infected with L. major a parasite showed The presence of severe steatosis of hepatocytes Hepatocyte degeneration, And loss of the radial arrangement of hepatocytes, With heavy infiltration in inflammatory cells, especially phagocytes( Macrophage) with Hyperplasia and congestion of the bile duct . As for histological sections of skin lesions taken from ear , Foot , tail ، were showed epidermal ulcerative , Accompanied by severe leaching of the dermis layer neutrophil ,polymorph lymphocytes ، with hemorrhage of ​​the dermis, with necrosis of the epidermal cells of all skin lesions in the ear, foot and tail.